"Different but connected": Participatory action research using Photovoice to explore well-being in autistic young adults. (July 2020) - Lam, Gary Yu Hin; Holden, Emily; Fitzpatrick, Megan; Raffaele Mendez, Linda; Berkman, Karen
Past research has largely focused on the negative aspects of well-being of autistic young adults during the post-school transition. Research that meaningfully includes autistic individuals and captures their perspectives of positive well-being is essential for stakeholders to better understand how to provide services that respond to the needs and wants of the autistic community. In the current study, 14 autistic young adults in a post-school transition program participated in a Photovoice project and used photos to express their ideas about well-being. A participatory action research approach was used to support participants' active engagement in the research processes and to encourage meaningful expression of their first-person perspectives. Results revealed an account of well-being reflecting expressions of individuality and growth, the significance of having close relationships, and a sense of connection with the community. This study has implications for research and practice that promotes well-being among the autistic community using approaches that are ethically informed and inclusive of autistic voices. Lay abstract: Past research has mainly focused on autistic people's deficits and poor outcomes compared to other groups of people. Little is known about their positive life experiences, and how to support them to achieve a higher quality of life. It is important to include autistic individuals in research so that they can influence how their voices are represented in a meaningful way and how the research results will be useful to them. In this study, a university researcher collaborated with 14 autistic young adults in a post-school transition program to design and run the research, collect and analyze the data, and use the results to create a presentation to the community. Specifically, the participants took photos in daily life and discussed their ideas about what a good life means to them. Results showed that these young adults described themselves as uniquely and different, but they were eager to learn and adapt. They also valued their relationships with their families, friends, and animals around them, as well as the community at large. This research shows that autistic individuals have important perspectives to share and knowledge to contribute when they are given the opportunities to participate in different aspects of research. The findings will be useful in developing services and influencing policies that promote well-being among autistic adults.